Primary school teachers’ assessment for learning practice for students’ learning improvement - Gebremariam, Hailay Tesfay; Gedamu, Abate Demissie (Frontiers in Education, 2023)
Assessment for learning practice and learning improvement are the two vital variables in this study. This article explores primary school teachers’ assessments for learning practices for student learning improvement. The participants (n = 242) were selected through a cluster random sampling techniques for a questionnaire survey from the target primary schools to meet the research objective of this study. Among the total participants 15 teachers for an in-depth interview, and five for informal conversations were randomly selected through purposive sampling. The data collected through closed-ended questionnaire were analyzed using mean, standard deviation, analysis of variance and post-hoc methods. To analyze the qualitative data acquired through interview and informal conversation, thematic verbal descriptions were employed. Conversely, the findings indicated that the primary school teachers had highly positive classroom environments practice, moderate positive learning intentions and success, feedback in assessment practices, and self- and peer-assessment practices toward learning assessment. Although, the findings from the quantitative data showed that the primary school teachers had high and moderate assessments for learning practice, the interviews revealed that they had low confidence in learning practice assessments owing to challenges faced during practice. These overall challenges relate to transparency, experience, training, school problems, and preference reliance. Finally, based on the study’s implications, recommendations are made for future directions of studies that will allow better comprehension of the assessment for learning practice in relation to the students’ learning improvement.